Нахождение производной функции

Erstellt am: 25. Januar 2025

Beantwortet mit O1 von Chat01

Frage

Опиши метод нахождения производной функции y=y(x).
Найдите производную функции y = y(x):
arctg(((1-x)/(1+x))^(1/2))
Найдите производную функции y = y(x):
arctg(x-(1+x^2)^(1/2))
Найдите производную функции y = y(x):
ln((x+(1-x^2)^(1/2))/x)
Найдите производную функции y = y(x):
e^(((1-x)/(1+x))^(1/2))

Gedanke

Describing derivative methods

I’m outlining the steps to systematically find derivatives, including the chain rule and product rule, in Russian for precise communication.

Mapping derivative steps

I'm using the quotient rule to differentiate u=1x1+xu = \sqrt{\frac{1-x}{1+x}}, simplify f(x)=1x1+xf(x) = \frac{1-x}{1+x}, and find f(x)f'(x).

Refining the expression

I’m meticulously simplifying 1(1+x)21x1+x\frac{-1}{(1+x)^2 \sqrt{\frac{1-x}{1+x}}} to achieve 1(1+x)3/21x-\frac{1}{(1+x)^{3/2} \sqrt{1-x}}.

Simplifying the steps

I’m laying out the process to derive dydx\frac{dy}{dx} by refining 12(1x)(1+x)\frac{1}{2\sqrt{(1-x)(1+x)}} to achieve 121x2-\frac{1}{2\sqrt{1-x^2}}.

Confirming consistency

I’m verifying the derivative dydx=121x2\frac{dy}{dx} = -\frac{1}{2\sqrt{1-x^2}} by checking signs and numerical values, ensuring it aligns with the function's behavior.

Confirming derivative precision

I’m checking the derivative near x=0x = 0 using a small difference quotient, confirming it’s close to -0.5, consistent with the function's behavior.

Analyzing known identities

I'm exploring trigonometric identities and algebraic expressions to simplify x1+x2x - \sqrt{1 + x^2} and the derivative, aiming to find a simpler form or constant expression.

Rewriting expressions

I’m working through transforming 1+x2x\sqrt{1+x^2} - x into a more digestible form, aiming to use known identities and simplify the derivative further.

Working through trigonometric identities

I’m factoring terms and attempting various trigonometric identities to simplify 1+u21 + u^2 to 21+x21+x2+x\frac{2\sqrt{1+x^2}}{\sqrt{1+x^2}+x}. Progress is steady and insightful.

Trying another way

I’m exploring different methods to simplify 1+u21 + u^2 and du/dxdu/dx, but progress remains steady. It's interesting to see what strategies might bring us closer to a solution.

Facilitating the process

OK, let me see. By factoring out 1+x2\sqrt{1+x^2} and using known identities, I’m simplifying 1+u21 + u^2 and du/dxdu/dx to streamline the derivative calculation.

Breaking down expressions

I’m piecing together how 1+u21 + u^2 and du/dxdu/dx simplify to a more straightforward form, using algebraic factorization and trigonometric identities, making the derivative calculation smoother.

Simplifying the derivative

I’m canceling out common factors in the numerator and denominator, leading to the simplified derivative 12(1+x2)\frac{1}{2(1+x^2)}.

Confirming the derivative

I'm checking the derivative at x=0x = 0 and using the difference quotient to ensure the calculation aligns with the function's behavior, leading to the confirmed derivative 12(1+x2)\frac{1}{2(1+x^2)}.

Confirming the derivative

I’m verifying the derivative at x=0x = 0 by calculating the difference quotient and using a Taylor expansion, confirming the result 12\frac{1}{2} as the precise slope.

Confirming the slope

OK, let me see. The difference quotient and Taylor expansion are confirming the slope's proximity to 0.5. This implies the derivative near x=0x = 0 aligns well with the function's behaviors.

Breaking down the process

I’m splitting y=ln(x+1x2)ln(x)y = \ln\left(x + \sqrt{1 - x^2}\right) - \ln(x) into simpler terms to find the derivative by calculating the derivatives of y1y_1 and y2y_2.

Breaking down and simplifying

I’m simplifying y1y_1' by factoring terms in the denominator, applying the difference of squares, and breaking down each expression to ensure everything is clear and accurate.

Combining fractions

I’m working through combining y1y_1' and y2y_2' into a single fraction, looking for known identities or trigonometric functions that might simplify the expression.

Rewriting the function

Transforming xx into sin(t)\sin(t) and cos(t)\cos(t), then simplifying the derivative through trigonometric identities and cot(t)\cot(t), makes me think progress is being made.

Verifying trigonometric identities

I’m carefully ensuring accurate steps by rechecking trigonometric identities and substitutions, leading to the derivative 1sin2(t)sin(t)cot(t)(1+cot(t))-\frac{1}{\sin^2(t) \sin(t) \cot(t) (1 + \cot(t))}.

Refining the approach

OK, let me see. I’m expressing trigonometric functions in terms of xx and ensuring all steps are accurate, leading to the derivative 1sin3(t)cot(t)[1+cot(t)]\frac{-1}{\sin^3(t) \cot(t) [1 + \cot(t)]}.

Piecing together the solution

OK, I’ll finalize by gathering all components, ensuring the derivative 1x1x2(x+1x2)\frac{-1}{x \sqrt{1 - x^2} (x + \sqrt{1 - x^2})} is accurately presented.

Verifying fractions

I’m gathering info to see if the derivative matches different approaches, like vector analysis and partial fractions, to confirm consistency. This involves testing trigonometric and algebraic methods.

Combining fractions

OK, let me see. I’m pulling together partial fractions and common denominators to simplify the derivative expression, ensuring all terms are accurately represented for a precise final form.

Simplifying expressions

Piecing together, the numerator simplifies to -1, leading to the final derivative expression 1x1x2(x+1x2)\frac{-1}{x \sqrt{1 - x^2} (x + \sqrt{1 - x^2})}, which confirms the expected behavior.

Confirming derivative accuracy

I’m checking the derivative 1x1x2(x+1x2)\frac{-1}{x \sqrt{1 - x^2} (x + \sqrt{1 - x^2})} against the trigonometric approach, ensuring consistency across methods.

Thought about нахождение производной функции for 1m 46s

Antwort

Ниже приведён план решения и подробные выкладки для каждой из заданных функций. Текст дан на русском языке.


1. Краткое описание общего метода дифференцирования y=y(x)y = y(x)

Чтобы найти производную функции y(x)y(x), обычно используют следующие правила:

  1. Правило суммы: ddx(u(x)+v(x))  =  u(x)+v(x).\frac{d}{dx}\bigl(u(x) + v(x)\bigr) \;=\; u'(x) + v'(x).
  2. Правило произведения: ddx(u(x)v(x))  =  u(x)v(x)+u(x)v(x).\frac{d}{dx}\bigl(u(x)\,v(x)\bigr) \;=\; u'(x)\,v(x) + u(x)\,v'(x).
  3. Правило частного: ddx(u(x)v(x))  =  u(x)v(x)u(x)v(x)[v(x)]2.\frac{d}{dx}\Bigl(\frac{u(x)}{v(x)}\Bigr) \;=\; \frac{u'(x)\,v(x) - u(x)\,v'(x)}{[\,v(x)\,]^2}.
  4. Правило цепочки (основное при сложных подстановках):
    Если y=f(u)y = f(u) и u=g(x)u = g(x), то dydx  =  f(u)g(x).\frac{dy}{dx} \;=\; f'(u)\,\cdot\,g'(x). Например, если y=ln(g(x))y = \ln\bigl(g(x)\bigr), то y=g(x)g(x)y' = \frac{g'(x)}{g(x)}.
    Если y=arctan(g(x))y = \arctan\bigl(g(x)\bigr), то y=g(x)1+[g(x)]2\displaystyle y' = \frac{g'(x)}{1 + [\,g(x)\,]^2}.
    Если y=eg(x)y = e^{g(x)}, то y=eg(x)g(x)\displaystyle y' = e^{g(x)}\,g'(x) и т.д.

В большинстве практических задач используется комбинация этих правил.


2. Найти производную

y=arctan ⁣(1x1+x).y = \arctan\!\Bigl(\sqrt{\tfrac{1 - x}{1 + x}}\Bigr).

Обозначим:

u(x)  =  1x1+x.u(x) \;=\; \sqrt{\frac{1 - x}{1 + x}}.

Тогда

y=arctan(u(x)).y = \arctan\bigl(u(x)\bigr).

По правилу цепочки:

y  =  11+u2    u(x).y' \;=\; \frac{1}{1 + u^2}\;\cdot\;u'(x).

Шаг 1. Находим u(x)u'(x)

u(x)  =  (1x1+x)12.u(x) \;=\; \Bigl(\frac{1 - x}{1 + x}\Bigr)^{\tfrac12}.

Обозначим

f(x)  =  1x1+x.f(x) \;=\; \frac{1 - x}{1 + x}.

Тогда u(x)=f(x)=[f(x)]1/2u(x) = \sqrt{f(x)} = [f(x)]^{1/2}. По правилу цепочки:

u(x)  =  12[f(x)]12f(x).u'(x) \;=\; \frac12\,\bigl[f(x)\bigr]^{-\tfrac12}\,\cdot\,f'(x).

Находим f(x)f'(x) (правило частного):

f(x)  =  (1+x)ddx(1x)    (1x)ddx(1+x)(1+x)2.f'(x) \;=\; \frac{(1 + x)\,\frac{d}{dx}(1 - x)\;-\;(1 - x)\,\frac{d}{dx}(1 + x)}{(1 + x)^2}. ddx(1x)=1,ddx(1+x)=1.\frac{d}{dx}(1 - x) = -1, \quad \frac{d}{dx}(1 + x) = 1.

Тогда

f(x)=(1+x)(1)    (1x)1(1+x)2=(1+x)    (1x)(1+x)2=1x1+x(1+x)2=2(1+x)2.f'(x) = \frac{(1 + x)\cdot (-1)\;-\;(1 - x)\cdot 1}{(1 + x)^2} = \frac{-\,(1 + x)\;-\;(1 - x)}{(1 + x)^2} = \frac{-1 - x - 1 + x}{(1 + x)^2} = \frac{-2}{(1 + x)^2}.

Значит,

u(x)=12(f(x))12(2(1+x)2)=1(1+x)2(f(x))12.u'(x) =\tfrac12\,\bigl(f(x)\bigr)^{-\tfrac12}\,\cdot\,\Bigl(-\frac{2}{(1 + x)^2}\Bigr) = -\,\frac{1}{(1 + x)^2}\,\bigl(f(x)\bigr)^{-\tfrac12}.

Но f(x)=1x1+xf(x) = \dfrac{1 - x}{1 + x}, а (f(x))1/2=11x1+x=1+x1x.\bigl(f(x)\bigr)^{-1/2} = \dfrac{1}{\sqrt{\tfrac{1 - x}{1 + x}}} = \sqrt{\frac{1 + x}{1 - x}}.

Отсюда

u(x)=1(1+x)21+x1x=1(1+x)3/21x.u'(x) = -\,\frac{1}{(1 + x)^2}\,\sqrt{\frac{1 + x}{1 - x}} = -\,\frac{1}{(1 + x)^{3/2}\,\sqrt{1 - x}}.

Шаг 2. Найдём 11+u2\tfrac{1}{1 + u^2}

u2=(1x1+x)2=1x1+x.u^2 = \Bigl(\sqrt{\tfrac{1 - x}{1 + x}}\Bigr)^2 = \frac{1 - x}{1 + x}.

Тогда

1+u2=1+1x1+x=(1+x)+(1x)1+x=21+x.1 + u^2 = 1 + \frac{1 - x}{1 + x} = \frac{(1 + x) + (1 - x)}{1 + x} = \frac{2}{1 + x}.

Следовательно,

11+u2=1+x2.\frac{1}{1 + u^2} = \frac{1 + x}{2}.

Шаг 3. Сочетаем всё вместе

y=11+u2u(x)=1+x2(1(1+x)3/21x).y' = \frac{1}{1 + u^2}\,u'(x) = \frac{1 + x}{2}\,\biggl(-\,\frac{1}{(1 + x)^{3/2}\,\sqrt{1 - x}}\biggr).

Упрощая,

y=1+x21(1+x)3/21x=121(1+x)1/21x=12(1x)(1+x)=121x2.y' = -\,\frac{1 + x}{2}\,\frac{1}{(1 + x)^{3/2}\,\sqrt{1 - x}} = -\,\frac{1}{2}\,\frac{1}{(1 + x)^{1/2}\,\sqrt{1 - x}} = -\,\frac{1}{2\,\sqrt{(1 - x)\,(1 + x)}} = -\,\frac{1}{2\,\sqrt{1 - x^2}}.

Итоговая производная:

dydx  =  121x2.\boxed{ \displaystyle \frac{dy}{dx} \;=\; -\,\frac{1}{2\,\sqrt{1 - x^2}}. }

3. Найти производную

y  =  arctan(x1+x2).y \;=\; \arctan\bigl(x - \sqrt{\,1 + x^2}\bigr).

Пусть

u(x)=x    1+x2.u(x) = x \;-\; \sqrt{1 + x^2}.

Тогда

y=arctan(u(x)),y=11+[u(x)]2u(x).y = \arctan\bigl(u(x)\bigr), \quad y' = \frac{1}{1 + \bigl[u(x)\bigr]^2}\,\cdot\,u'(x).

Шаг 1. Найдём u(x)u'(x)

u(x)=ddx(x1+x2)=1ddx1+x2.u'(x) = \frac{d}{dx}\Bigl(x - \sqrt{1 + x^2}\Bigr) = 1 - \frac{d}{dx}\sqrt{1 + x^2}. ddx1+x2=121+x22x=x1+x2.\frac{d}{dx}\sqrt{1 + x^2} = \frac{1}{2\,\sqrt{1 + x^2}}\cdot 2x = \frac{x}{\sqrt{1 + x^2}}.

Значит,

u(x)=1x1+x2.u'(x) = 1 - \frac{x}{\sqrt{1 + x^2}}.

Шаг 2. Упростим [1+(x1+x2)2]\bigl[1 + (x - \sqrt{1 + x^2})^2\bigr]

Обозначим u=x1+x2u = x - \sqrt{1 + x^2}. Тогда

u2=x2    2x1+x2  +  (1+x2).u^2 = x^2 \;-\; 2x\,\sqrt{1 + x^2}\;+\;(1 + x^2).

Поэтому

1+u2=1+x2+1+x2    2x1+x2=2+2x2    2x1+x2.1 + u^2 = 1 + x^2 + 1 + x^2 \;-\; 2x\,\sqrt{1 + x^2} = 2 + 2\,x^2 \;-\; 2\,x\,\sqrt{1 + x^2}.

Можно вынести 2:

1+u2=2(1+x2x1+x2).1 + u^2 = 2\Bigl(\,1 + x^2 - x\,\sqrt{1 + x^2}\Bigr).

Однако удобнее заметить следующую «хитрую» упрощённую форму. Рассмотрим пошагово:

  • В числителе при цепочечной формуле у нас стоит u(x)=1x1+x2u'(x) = 1 - \tfrac{x}{\sqrt{1 + x^2}}.
  • Окажется, что если аккуратно записать дробь u(x)1+u2\dfrac{u'(x)}{1 + u^2} и сократить, получится очень простое выражение.

Быстрый способ (через алгебраическое тождество) даёт результат:

ddxarctan(x1+x2)  =  12(1+x2).\frac{d}{dx}\arctan\bigl(x - \sqrt{1 + x^2}\bigr) \;=\; \frac{1}{2\,(1 + x^2)}.

Ниже — краткий «чистый» вывод.

Короткий вывод с упрощением

  1. (u'(x) = 1 - \dfrac{x}{\sqrt{1 + x^2}} = \dfrac{\sqrt{1 + x^2} - x}{\sqrt{1 + x^2}}.)

  2. (;1 + \bigl[x - \sqrt{1 + x^2}\bigr]^2 = 2,\sqrt{1 + x^2},\bigl(\sqrt{1 + x^2} - x\bigr)) (это можно показать путём факторизаций).

Тогда

u(x)1+u2=1+x2x1+x221+x2(1+x2x)  =  1+x2x1+x2    121+x2(1+x2x).\frac{u'(x)}{1 + u^2} = \frac{\dfrac{\sqrt{1 + x^2} - x}{\sqrt{1 + x^2}}} {2\,\sqrt{1 + x^2}\,\bigl(\sqrt{1 + x^2} - x\bigr)} \;=\; \frac{\sqrt{1 + x^2} - x}{\sqrt{1 + x^2}} \;\cdot\; \frac{1}{2\,\sqrt{1 + x^2}\,\bigl(\sqrt{1 + x^2} - x\bigr)}.

Фактор (1+x2x)(\sqrt{1 + x^2} - x) сокращается, и остаётся:

=12(1+x2).= \frac{1}{2\,\bigl(1 + x^2\bigr)}.

Таким образом,

y=12(1+x2).\boxed{ \displaystyle y' = \frac{1}{2\,(1 + x^2)}. }

4. Найти производную

y  =  ln ⁣(x+1x2x).y \;=\; \ln\!\Bigl(\,\frac{x + \sqrt{\,1 - x^2}}{\,x\,}\Bigr).

Перепишем логарифм как разность:

y=ln(x+1x2)    ln(x).y = \ln\bigl(x + \sqrt{1 - x^2}\bigr)\;-\;\ln(x).

Тогда

y=ddxln(x+1x2)    ddxln(x).y' = \frac{d}{dx}\ln\bigl(x + \sqrt{1 - x^2}\bigr) \;-\; \frac{d}{dx}\ln(x).

Шаг 1. Производная первой части

ddxln(x+1x2)=1x+1x2  ×  ddx(x+1x2).\frac{d}{dx}\,\ln\bigl(x + \sqrt{1 - x^2}\bigr) = \frac{1}{x + \sqrt{1 - x^2}} \;\times\; \frac{d}{dx}\Bigl(x + \sqrt{1 - x^2}\Bigr).

А

ddx(x+1x2)=1+ddx1x2=1+121x2(02x)=1x1x2.\frac{d}{dx}\Bigl(x + \sqrt{1 - x^2}\Bigr) = 1 + \frac{d}{dx}\sqrt{1 - x^2} = 1 + \frac{1}{2\,\sqrt{1 - x^2}}\cdot \bigl(0 - 2x\bigr) = 1 - \frac{x}{\sqrt{1 - x^2}}.

Значит, производная:

1x1x2x+1x2=1x2x1x2  /  (x+1x2).\frac{1 - \tfrac{x}{\sqrt{1 - x^2}}} {\,x + \sqrt{1 - x^2}\,} = \frac{\sqrt{1 - x^2} - x}{\sqrt{1 - x^2}} \;\Big/\; \bigl(x + \sqrt{1 - x^2}\bigr).

То есть

=1x2x1x2(x+1x2).= \frac{\sqrt{1 - x^2} - x} {\sqrt{1 - x^2}\,\bigl(x + \sqrt{1 - x^2}\bigr)}.

Шаг 2. Производная второй части

ddxln(x)=1x.\frac{d}{dx}\ln(x) = \frac{1}{x}.

Шаг 3. Разность

y=1x2x1x2(x+1x2)    1x.y' = \frac{\sqrt{1 - x^2} - x} {\sqrt{1 - x^2}\,\bigl(x + \sqrt{1 - x^2}\bigr)} \;-\; \frac{1}{x}.

Приведём к общему знаменателю x1x2(x+1x2)x\,\sqrt{1 - x^2}\,(x + \sqrt{1 - x^2}). Подробно можно расписать, но результат (после аккуратных сокращений) получается весьма компактный:

y=1x1x2(x+1x2).\boxed{ y' = -\,\frac{1} {\,x\,\sqrt{1 - x^2}\,\bigl(x + \sqrt{1 - x^2}\bigr)}. }

Проверка: при подробном сведении к общему знаменателю числитель оборачивается в 1-1. Это можно также увидеть из тригонометрических подстановок x=sintx = \sin t, но итог тот же.


5. Найти производную

y=e1x1+x.y = e^{\sqrt{\tfrac{1 - x}{1 + x}}}.

Обозначим

u(x)  =  1x1+x.u(x) \;=\; \sqrt{\frac{1 - x}{1 + x}}.

Тогда

y=eu(x),y=eu(x)    u(x).y = e^{u(x)}, \quad y' = e^{u(x)}\;\cdot\;u'(x).

Из задачи № 2 мы уже нашли аналогичную производную для 1x1+x\sqrt{\tfrac{1 - x}{1 + x}}. Результат был:

u(x)=1(1+x)3/21x.u'(x) = -\,\frac{1}{(1 + x)^{3/2}\,\sqrt{1 - x}}.

Отсюда

y=e1x1+x  ×  (1(1+x)3/21x)  =  e1x1+x(1+x)3/21x.\boxed{ y' = e^{\sqrt{\frac{1 - x}{1 + x}}} \;\times\; \Bigl(\,-\,\frac{1}{(1 + x)^{3/2}\,\sqrt{1 - x}}\,\Bigr) \;=\; -\,\frac{e^{\sqrt{\frac{1 - x}{1 + x}}}} {(1 + x)^{3/2}\,\sqrt{1 - x}} .}

Итоговые ответы

  1. Общий метод: использовать стандартные правила дифференцирования (суммы, произведения, частного, цепочки) и таблицу производных элементарных функций (lnx,  ex,  sinx,  arctanx,  x\bigl(\ln x,\; e^x,\; \sin x,\; \arctan x,\; \sqrt{x} и т.д.).

  2. y=arctan ⁣(1x1+x)\displaystyle y = \arctan\!\Bigl(\sqrt{\tfrac{1 - x}{1 + x}}\,\Bigr)

y=121x2.y' = -\,\frac{1}{2\,\sqrt{1 - x^2}}.
  1. y=arctan(x1+x2)\displaystyle y = \arctan\Bigl(x - \sqrt{\,1 + x^2}\Bigr)
y=12(1+x2).y' = \frac{1}{2\,(1 + x^2)}.
  1. y=ln ⁣(x+1x2x)\displaystyle y = \ln\!\Bigl(\,\frac{x + \sqrt{1 - x^2}}{\,x\,}\Bigr)
y=1x1x2(x+1x2).y' = -\,\frac{1}{\,x\,\sqrt{1 - x^2}\,\bigl(x + \sqrt{1 - x^2}\bigr)}.
  1. y=e1x1+x\displaystyle y = e^{\,\sqrt{\tfrac{1 - x}{1 + x}}}
y=e1x1+x  ×  (1(1+x)3/21x)=  e1x1+x(1+x)3/21x.y' = e^{\sqrt{\frac{1 - x}{1 + x}}} \;\times\; \biggl(-\,\frac{1}{(1 + x)^{3/2}\,\sqrt{1 - x}}\biggr) =\; -\,\frac{e^{\sqrt{\frac{1 - x}{1 + x}}}} {(1 + x)^{3/2}\,\sqrt{1 - x}}.

Все производные получены с учётом правил дифференцирования и упрощены.

Diesen Q&A teilen